KARAKTERISTIK PAPAN PARTIKEL CAMPURAN LIMBAH KAYU SENGON DAN BAGAS SORGUM MENGGUNAKAN PEREKAT ASAM SITRAT - Jajang Sutiawan; Suci Mardhatillah; Dede Hermawan; Firda A Syamani; Subyakto; Sukma S Kusumah (BRIN Publishing, 2020)
Waste of sengon wood could be used as an alternative material in the manufacture of particleboards. However,particleboards made from sengon has seome inferior physical and mechanical properties, which did not meet the Japanesestandard (JIS A 5908: 2003). The aim of this research is to improve the physical and mechanical properties ofsengon particleboard using sorghum bagasse in various raw material composition using citric acid adhesives. Citric acidwas used as a binding agent with 20% adhesive content based on the weight of the air-dried particle. Compositionof fiber mixtures between sengon and bagasse sorghum were set in 100:0, 75:25, 50:50, and 25:75 wt.%. Thetargetted density of particleboard was set at 0.80 g/cm3. The hot-pressing conditions of particleboard manufacturingwere 200°C for 10 min. The physical and mechanical properties of the particleboards were evaluated according toJIS A 5908: 2003 standard. The results showed that the density, moisture content, thickness swelling, modulus ofelasticity, modulus of rupture and internal bond met the requirements of the JIS A 5908-2003 standard. Thus, theadditional of bagasse sorghum becomes an alternative way to enhance the physical and mechanical properties of sengonparticleboard. The addition 75% bagasse sorghum had better moisture content, water absorption, thickness swelling,modulus of elasticity, and modulus of rupture of particleboard.